Analisis Pencemaran Air Sungai Cigayam Kabupaten Cirebon Akibat Pembuangan Limbah Industri Batu Alam - Salsabilla, Bella; Retnowati, Rita; Istiana, Rita (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M), 2024)
One of the problems in rivers is water pollution due to the discharge of waste directly into the river, which can reduce the quality of river water. The large number of natural stone processing activities in Dukupuntang District has the potential to become a source of river water pollution. The aim of this research is to analyze river water pollution due to the disposal of natural stone industrial waste in terms of physical, chemical and biological parameters, as well as determine the impact of river water pollution due to the disposal of natural stone industrial waste on the water quality of the Cigayam River. This research was carried out in Cangkoak Village, Dukupuntang District, Cirebon Regency. This research analyzes physical parameters (temperature, water brightness, water color, water smell, current speed), chemical parameters (pH, DO, BOD, COD) which are compared with class IV water quality standards based on Republic of Indonesia Government Regulation No. 22 of 2021 about Implementation of Protection and Enviromental Management, biological parameters (macroinvertebrates) identified using the electronic book Introduction to Southeast Asian Pond and River Invertebrates. The research results showed a decrease in river water quality with several test parameters that exceeded quality standards, namely pH, DO, BOD, COD. The water quality index value at stations 1 and 2 shows moderately polluted water quality, while station 3 shows dirty polluted water quality. This explains that the disposal of natural stone waste directly into rivers causes a decrease in water quality, one of which is due to the content of chemicals, such as metal elements or salts which can affect water quality. Thus, the pollution level of the Cigayam River is included in the moderate pollution level.